Designing Work Within and Between Organizations - Sinha, Kingshuk K.; Van de Ven, Andrew H. (Organization Science, 2005)
The design of work has been and will continue to be a central problem challenging organization theory and practice. The system of arrangements and procedures for doing work affects all workers every day throughout the world. Work is changing dramatically. In an increasingly global and knowledge-intensive economy, work design is no longer contained within an organization; it often transcends the boundaries of organizations and countries. These changes call for a renewed research focus on work design. Building on configuration and complexity perspectives, we propose a framework for studying work design. We argue that three issues require attention to advance the knowledge of work design: (1) defining the boundaries of work systems, (2) examining how the system is nested in a hierarchy within and between organizations, and (3) determining interactions between the elements of a work system. We propose a method of frontier analysis for identifying equifinal designs—the set of equally effective work designs for different combinations of inputs (situations or contexts) and outputs (performance criteria). When work designs are examined longitudinally, these methods permit an examination of adaptation processes on changing fitness landscapes, suggesting how work systems may increase, decrease, or sustain their relative performance over time.